RISK FACTORS AND PECULIARITIES OF NUTRITION OF INFANTS WITH CHRONIC DIARRHEA - T.S. Lazareva; F.F. Zhvaniya ("Paediatrician" Publishers LLC, 2008)
Results of observation of children from 2,5 months to 4 years old, treated in hospital with diagnosis chronic diarrhea are analyzed in this article. Diarrhea debuted in first year of living in most cases. The reason of onset of diarrhea often was alimentary factor. Hereditary predisposition, pathologic pregnancy, and diseases in women at the time of pregnancy played an important role in development of disease. Nutrition of children in early age was characterized by low duration of breast feeding and early conversion of children to the mixed and artificial feeding. Main food stuffs in children's nutrition on mixed and artificial feeding was adapted milk formulas, and rarely non adapted milk food (cow's and goat's milk, kefir). Only 30% of mothers had a definite knowledge of proper child's feeding and advantages of breast feeding. This fact indicates necessity of more active educational work by medical staff.Key words: children, chronic diarrhea, nutrition.